Metaphor and the Reshaping of Our Cognitive Fabric - Birner, Betty J. 19XX- (Zygon, 2004)
Mary Gerhart and Allan Russell view our world of meanings as a fabric of concepts and relations. Metaphor bends this fabric, superimposing one concept on another. While Gerhart and Russell are right to view metaphor as a cognitive rather than a purely linguistic phenomenon, their model misses the danger inherent in a cognitive restructuring that leaves some features of a concept highlighted and others backgrounded. When the bending of the conceptual fabric becomes permanent, the essential metaphorical insight is lost, leaving a skewed understanding of reality. We have a tendency to retain the metaphorically altered cognitive topography while forgetting its nonliteral genesis. Thus, the metaphoric process is one from which proceeds not only insight but also, necessarily, misconception.